Efektivitas Vaksinasi Rubella Dalam Pengendalian Congenital Rubella Syndrome (CRS) - Indah Laily Hilmi; Salman Salman; Riani Riani (Publikasi Indonesia, 2022)
Measles or rubella is an infectious viral infectious disease that is a public health problem globally. Congenital Rubella Syndrome (CRS) is a disease in infants caused by infection of the fetus with the rubella virus during pregnancy. CRS therapy that can be done today is by giving rubella vaccination to children, adolescents, and adult women. To determine the effectiveness of the rubella vaccine in preventing and controlling CRS cases, an article review was carried out with a literature study using secondary data in the form of journals/articles, and books. Search the database of journals and articles retrieved through the internet through the google scholar database. Based on several journal results studied, it was concluded that rubella vaccination is effective and safe to prevent and control CRS cases.